PEMURNIAN MONO-DIASILGLISEROL HASIL ESTERIFIKASI PALM FATTY ACID DISTILLATE DAN GLISEROL DENGAN EKSTRAKSI PELARUT-SAPONIFIKASI DAN DISTILASI MOLEKULER - Riri Mardaweni, Dwi Setyaningsih, dan Meika Syahbana Rusli (Jurnal Teknologi Industri Pertanian, 2017)
Mono-diacylglycerol (M-DAG) is one of potential palm oil derived products to be developed. Palm Fatty Acid Distillate (PFAD) and glycerol esterification using Methyl Ester Sulfonic Acid (MESA) catalyst produced M-DAG that consist of Free Fatty Acid (FFA) and Triacylglycerol (TAG) fractions. FFA and TAG fractions can reduce the M-DAG emulsifier quality. Therefore, purification process is needed to eliminate FFA and TAG fractions. The purpose of this research was to improve the M-DAG emulsifier quality by purification process. The purification was performed in two ways: solvent extraction - saponification and molecular distillation. Solvent extraction - saponification was done with the addition of 0, 10, 15 and 20% (w/w) NaHCO3. The result showed that the addition of 20% (w/w) NaHCO3 was the best treatment. It was able to produce 43.52% yield of M-DAGconsisted of 44.48% Thin-Layer Chromatography (TLC) in FFA+TAG composition, 31.05% MAG, 24.47% DAG, melting point of 44.83oC, free fatty acid level of 19.43%, pH value of 6, emulsion stability of 51.21% for 12 hours, has a white color, dry texture, and odorless. The molecular distillation at temperature of 100-180oC on purification process was carried out to separatethe FFA. Molecular distillation had produced distillate and residue. Molecular distillation was an effective process to separate the FFA from M-DAG whereas produced 96.09% of FFA from distillation flow.Keywords : glycerol, molecular distillation, palm fatty acid distillate, purification, saponification